Uma análise sobre as dificuldades de avaliar incertezas e riscos jurídico-tributários e seus impactos contábeis e práticos - Ribeiro, Rodrigo Bernardes (2016)
The present work aims to examine the risks and legal uncertainties and see how companies approach, treat and mitigate them, and how eventually this can be improved, especially in tax matters, considering the importance of its evaluation to record liabilities on financial reports, the practical effects of tax discussions and the impact of losing major litigation on taxpayers. It also seeks to elucidate the difficulties, mainly from the analysis of relevant tax discussions that are observed on the national scene and that occupy the most important courts in Brazil, and objectively point the accounting rules that must be observed by companies and the mechanisms which are usually used by them to ensure the quality of accounting judgments and consequently the information provided to external users. Given that accounting standards suggest that companies can rely on expert opinions and the perception that the opinions of lawyers have great relevance on legal risk evaluation, especially on tax matters, we analyze the way they are issued and what level of objectivity and accuracy can be expected from the loss or gain prognoses portrayed in them, to conclude that, although not as accurate, this tool is still the best mechanism available, given the peculiarities and uncertainties inherent in the law and the very indeterminacy of the future. Nevertheless, taking into account the basic characteristics of the risks, we beliebe that the knowledge of other areas on risk management, such as project management, can be adapted to law, in addition (and not replacement) to the legal opinions and the governance processes already implemented by the companies. Some tools that we consider capable of being applied to law are: (a) analysis of root causes and consequences; (B) numerical Linkert scale, combined with risks exposure in lists evaluated qualitatively; (C) Delphi technique. Finally, we present some practical effects of uncertainties and legal risks on tax matters and difficulties of its evaluation, to draw attention to the need of its management, as it is impossible to eliminate them.